2011
DOI: 10.1002/ana.22421
|View full text |Cite
|
Sign up to set email alerts
|

The blood–spinal cord barrier: Morphology and Clinical Implications

Abstract: The blood-spinal cord barrier (BSCB) is the functional equivalent of the blood-brain barrier (BBB) in the sense of providing a specialized microenvironment for the cellular constituents of the spinal cord. Even if intuitively the BSCB could be considered as the morphological extension of the BBB into the spinal cord, evidence suggests that this is not so. The BSCB shares the same principal building blocks with the BBB; nevertheless, it seems that morphological and functional differences may exist between them.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
324
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(342 citation statements)
references
References 133 publications
4
324
0
2
Order By: Relevance
“…Similarly to the blood-brain barrier (BBB), BSCB plays a protective and regulatory role in spinal cord parenchyma. Endothelial cells, basement membranes, pericytes, and astrocytic end-feet processes constitute a specialized system for this functional barrier [5]. Early microvascular reactions and BSCB disruption are instrumental in the pathophysiology of SCI and repair [6,7].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Similarly to the blood-brain barrier (BBB), BSCB plays a protective and regulatory role in spinal cord parenchyma. Endothelial cells, basement membranes, pericytes, and astrocytic end-feet processes constitute a specialized system for this functional barrier [5]. Early microvascular reactions and BSCB disruption are instrumental in the pathophysiology of SCI and repair [6,7].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…However, the potential toxic effects, especially under 168 pathological conditions, are notable. Though the permeability of the BBB may 169 be spontaneously enhanced at certain time-windows post-injury, as for 170 example after Traumatic Brain or Spinal Cord Injury (Bartanusz et al 2011), 171 that will allow the desired drugs entering the CNS, the pharmacological 172 disruption of the BBB under pathological conditions may in contrast worsen 173 the disease progression. For instance, the pharmacological disruption of the 174 BBB enhanced the clinical severity in an EAE model (Alvarez et al 2011), 175…”
Section: The Delivery Of Substances Across the Blood Cerebrospinal Flmentioning
confidence: 99%
“…In this context, the dysfunction of the BBB and BSCB 177 has been well documented in the etiology or progression of several CNS 178 pathologies (Bartanusz et al 2011), making the enhancement of BBB barrier 179 permeability not indicated for the delivery of drugs into the damaged CNS. Parkinson's disease (Wade and Katzman 1975).…”
Section: The Delivery Of Substances Across the Blood Cerebrospinal Flmentioning
confidence: 99%
“…The blood-brain barrier (BBB) and blood-spinal cord barrier (BSCB) are composite structures the role of which is selective separation of the cerebral and spinal parenchyma from the contents of the blood vessel; these barriers play both a protective and regulatory role for the respective central nervous system (CNS) parenchyma [3]. The blood-brain barrier and BSCB are prone to damage from insults of varying origin, including local inflammatory processes, ischemia, hypoxia, mechanical trauma, and more.…”
Section: Introductionmentioning
confidence: 99%
“…These differences may be responsible for diverse susceptibility of BBB and BSCB to some pathological conditions [3]. Many authors suggest that disruption of BSCB or alteration of its permeability may be of key importance for the consequences of acute injury of the spinal cord [47] and for the development of some CNS pathologies, such as multiple sclerosis [37], amyotrophic lateral sclerosis [15,29], spinal cord ischemia [16,18,27], and neuropathic pain [4].…”
Section: Introductionmentioning
confidence: 99%